Green synthesis and characterization of nano selenium using the extract of Phyllanthus emblica - S. Reema Sagitha; V. Aravindan; J. Suvetha Rani; M. Mahendran (Measurement: Energy)
To maintain the health of humans, animals, and microorganisms, selenium is a trace and essential micronutrient. Selenium nanoparticles (Se-NPs) have recently garnered the attention of numerous researchers as a result of their outstanding biocompatibility, low toxicity and significant bioavailability. Due to their increased bioactivity, Se-NPs finds extensive use in a variety of biomedical applications. Phyllanthus emblica (an Indian gooseberry) was employed as a stabiliser and reducer in the development of a straightforward method for the synthesis of Se-NPs in the present study. Fourier Transform Infrared Spectroscopy (FT-IR) and UV–Visible Spectroscopy were employed to characterize the synthesized selenium nanoparticles, including their optical properties. The synthesized nanoparticles photocatalytic degradation efficiency was investigated using Methylene Blue (MB) Dye. We tested the antibacterial properties of the synthesized Se-NPs against both gram-positive and gram-negative bacteria using the disc diffusion method. The synthesized Se-NPs demonstrated significant inhibition and antibacterial activity against both gram-positive and gram-negative isolates.